ANALISIS HUKUM PUTUSAN HAKIM PERKARA CERAI TALAK NOMOR 1098/Pdt.G/2021/PA.Bn DALAM TINJAUAN UNDANG-UNDANG NOMOR 50 TAHUN 2009 DAN HUKUM ISLAM - Sari, Rina Puspita (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2022)
Abstract: This study discusses two main studies of the case, namely: 1) What is the Status of Case Number 1098/Pdt.G/2021/ PA.Bn in Law Number 50 of 2009? 2) What is the position of Case 1098/Pdt.G/2021/PA.Bn in the Nebis In Idem review? 3) What about Case Number 1098/Pdt.G/2021/PA.Bn in the Perspective of Islamic Law?. These three issues are discussed using a normative legal research type with a literature study. The approaches used in this research are case approach, statutory approach, and analytical approach. The results of this study are 1) The position of the decision of the case Number 1098/ Pdt.G/2021/PA.Bn in the perspective of Law Number 50 of 2009 concerning Religious Courts, is textually contrary to Article 70 paragraph (6) of Law Number 50 of 2009 concerning Religious Courts. 2) The decision on the talak divorce case Number 1098/Pdt.G/2021/PA.Bn, when viewed from the ne bis in idem principle, has fulfilled the requirements for the application of the ne bis in idem principle in this case. 3) Decision on Case Number 1098/Pdt.G/2021/PA.Bn Islamic Law Perspective, the position of the decision on case Number 1098/Pdt.G/2021/PA.Bn which has been determined by the Bengkulu Religious Court Judge Class 1 A is in accordance with the law Islam, because in the legal considerations of the decision, the judge avoids more severe harm if the marriage is continued, then the judge seeks benefit and prioritizes justice by continuing to accept the case by setting aside statutory regulations solely for the sake of justice, certainty and benefit of the parties. Keywords: Judge’s Decision, Divorce Divorce, Nebis In Idem Principle, Law Number 50 Year 2009, and Islamic Law. Abstrak: Penelitian ini membahas dua kajian pokok perkara yaitu: 1) Bagaimana Kedudukan Perkara Nomor 1098/Pdt.G/2021/ PA.Bn dalam Undang-Undang Nomor 50 Tahun 2009? 2) Bagaimana kedudukan Perkara 1098/Pdt.G/2021/PA.Bn dalam tinjauan Nebis In Idem? 3) Bagaimana Perkara Nomor 1098/Pdt.G/2021/PA.Bn dalam Perspektif Hukum Islam?. Tiga permasalahan ini dibahas dengan menggunakan jenis penelitian hukum normatif dengan studi kepustakaan. Adapun pendekatan yang digunakan dalam penelitian ini adalah pendekatan kasus, pendekatan perundang-undangan, dan pendekatan analitis. Hasil dari penelitian ini ialah 1) Kedudukan putusan perkara Nomor 1098/Pdt.G/2021/PA.Bn dalam perspektif Undang-undang Nomor 50 Tahun 2009 tentang Peradilan Agama, secara tekstual memang bertentangan dengan Pasal 70 ayat (6) Undang-undang Nomor 50 Tahun 2009 tentang Peradilan Agama. 2) Putusan perkara cerai talak Nomor 1098/Pdt.G/2021/PA.Bn ini jika ditinjau dari asas ne bis in idem, telah memenuhi syarat berlakunya asas ne bis in idem dalam perkara ini. 3) Putusan Perkara Nomor 1098/Pdt.G/2021/PA.Bn Perspektif Hukum Islam, kedudukan putusan perkara Nomor 1098/Pdt.G/2021/PA.Bn yang telah ditetapkan oleh Hakim Pengadilan Agama Bengkulu Kelas 1 A telah sesuai dengan hukum Islam, karena dalam pertimbangan hukum putusan itu, hakim menghindari kemudharatan yang lebih parah jika pernikahan itu dilanjutkan, maka hakim mencari kemaslahatan dan mengedepankan keadilan dengan tetap menerima perkara tersebut dengan mengenyampingkan peraturan perundang-undangan semata-mata demi keadilan, kepastian dan kemanfaatan para pihak. Kata Kunci : Putusan Hakim, Cerai Talak, Asas Nebis In Idem, UU Nomor 50 Tahun 2009 dan Hukum Islam